Treatment Patterns, Effectiveness, and Safety of Originator Insulin Glargine versus Insulin Glargine-yfgn within the Veterans Health Administration - Samantha Walczuk; Francesca E. Cunningham; Xinhua Zhao; Diane Dong; Peter A. Glassman; Donald R. Miller; Deborah Khachikian; Anthony Au; Cedric Salone; Kelly Bryan; Qoua Her; Sherrie L. Aspinall (MDPI AG, 2024)
We described insulin glargine (originator) and insulin glargine-yfgn (biosimilar) treatment patterns, assessed effectiveness and safety outcomes, and identified reasons for switching back to the originator product from the biosimilar. This retrospective study included 328,463 Veterans 18 years of age and older who received one or more outpatient prescriptions for insulin glargine and/or insulin glargine-yfgn between 1 June 2021 and 31 December 2022. Patients were assigned to subgroups based on the initial prescription during the study period, prevalent versus incident use for originator insulin glargine, and prior versus no prior use of the originator before the biosimilar (i.e., prevalent originator non-switcher (n = 189,734), originator switch to biosimilar (n = 81,010), incident originator non-switcher (n = 49,401), and incident biosimilar (n = 8318)). There were no differences in the outcome of mean HbA1c (7.9% for all subgroups). There were also no differences in the unadjusted rates of hospitalization and/or emergency room visits for hyper- and hypoglycemia between the prevalent originator non-switcher and originator switched to biosimilar subgroups (p = 0.09 and 0.38, respectively) or the incident originator non-switcher and incident biosimilar subgroups (p = 0.054 and 0.61, respectively). Finally, none of the HbA1c or hyperglycemia outcomes adjusted for baseline characteristics were statistically different. Adjusted analyses for rates of hospitalization and/or emergency room visits for hypoglycemia could not be performed due to the low number of events. Overall, patients who received insulin glargine-yfgn had similar effectiveness and safety outcomes as patients who received the originator.